[(–)-(1S,2S)-N,N′-Bis(2-oxidobenzylidene)-1,2-diphenylethane-1,2-diamine]bis(pyridine)cobalt(III) perchlorate methanol hemisolvate hemihydrate - Chen, Yu-Ting (International Union of Crystallography, 2008)
In the title compound, [Co(C(28)H(22)N(2)O(2))(C(5)H(5)N)(2)]ClO(4)·0.5CH(4)O·0.5H(2)O, each Co(III) ion is coordinated by the tetradentate N,N′-bis(2-oxidobenzylidene)-1,2-diphenylethane-1,2-diamine ligand [Co—N = 1.900 (3) and 1.903 (3) Å; Co—O = 1.885 (3) and 1.891 (3) Å] and two pyridine ligands [Co—N = 1.967 (4) and 1.977 (3) Å] in a distorted octahedral geometry. The packing of the cations and anions forms voids of 258 Å(3), which are filled by methanol and solvent water molecules with half occupancies. O—H⋯O hydrogen bonds between solvent molecules, perchlorate anions and water molecules, and between water molecules and O atoms of the ligand, help to consolidate the crystal packing.